Handbook of research on transnational higher education - Mukerji, Siran; Tripathi, Purnendu 1975- (Advances in higher education and professional development (AHEPD) book series, 2014)
"This book is a unique compilation of the most recent research done by higher education professionals in the areas of policy, governance, technology, marketing, and leadership development, highlighting the most important strategies and policies for professionals, policy makers, administrators, and researchers interested in higher education management"--Provided by publisher